Clinical and immunologic features of the phenotype of systemic lupus erythematosus combined with Sjögren's syndrome - S. K. Solovyev; E. A. Aseeva; A. A. Baranov; A. M. Lila; N. Yu. Nikishina; S. I. Glukhova (Современная ревматология, 2023)
The problem of clinical and immunological heterogeneity of systemic lupus erythematosus (SLE) is of great interest, especially the combination of SLE and Sjögren's syndrome (SjS) determines a more favorable prognosis and specifics of therapy.Objective: to characterize the clinical and immunological features of SLE combined with SjS.Material and methods. The retrospective study included 44 patients with SLE combined with SjS and 356 patients with SLE without SjS, hospitalized at the V.A. Nasonova Research Institute of Rheumatology between 2013 and 2021. The two groups of patients were compared in terms of life expectancy, clinical manifestations, laboratory parameters and therapy.Results and discussion. The following phenotypic features of the clinical and immunological variant of SLE combined with SjS were found: significantly longer duration of SLE (p<0.01); higher incidence of polyarthritis (p=0.01) and Raynaud's syndrome (p<0.003) at disease onset. Subacute cutaneous lupus erythematosus, Raynaud's syndrome, peripheral nervous system involvement (sensory polyneuropathy and distal sensory-motor polyneuropathy) were found more frequently in SLE combined with SjS than in SLE without SjS, p<0.0001. Among laboratory abnormalities in SLE patients with SjS, leukopenia (p<0.0001), antibodies to SSA/Ro, SSB/La, and rheumatoid factor (p<0.0001) were observed in a greater number of cases. In the group of SLE combined with SjS, the chronic variant of SLE course according to the classification of V.A. Nasonova, and lower activity were observed, which didn't not require therapy with high doses of glucocorticoids; in this group, rituximab (p<0.01), cyclophosphamide and methotrexate were used significantly more often.Conclusion. Thus, significant clinical and laboratory differences were found between SLE with SjS and without SjS. They determine prognosis, approaches to pathogenetic therapy and monitoring.